The Application of Information Services Through Film Media to Students' Social Interaction - Nurwahida Alimuddin; Samintang Samintang; Muhammad Sarib Abdul Rasak; Taufik Taufik; Siti Rahmi (International Journal of Administration and Education (IJAE), 2026)
This study aims to determine the influence of information services using film media on the social interaction of class X students at SMA Negeri 4 Palu. This study uses a quantitative approach with a pre-experimental design of the type of one group pretest–posttest design. The research sample amounted to 37 students selected from class X. Data collection was carried out using a social interaction scale that included aspects of social contact and communication. Data analysis used descriptive and inferential statistics with a paired sample t-test. The results of the descriptive analysis showed that there was a change in the level of social interaction of students before and after treatment. The average pretest score of 66.35 increased to 68.05 in the posttest. The results of the hypothesis test showed a significance value of 0.000 < 0.05 which means that there is a significant difference between the pretest and posttest scores. These findings show that information services using film media influence increasing students' social interaction. Thus, film media can be used as an alternative strategy in guidance and counseling services to help students improve their social interaction skills in the school environment